2020
DOI: 10.3390/vaccines8010052
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Influenza Vaccine Uptake and Its Determinants among University Students: A Cross-Sectional Study

Abstract: While vaccination is the only established option to prevent a susceptible host from influenza, we have yet to clarify the decision-making mechanisms of vaccine uptake among Japanese university and college students. We aimed to explore vaccination coverage and the related demographic, sociocultural, and socioeconomic factors among university students. We performed a cross-sectional survey involving 604 students at Hokkaido University. Participants were asked if they received influenza vaccination in advance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Although this apparent increase in the vaccination rate among medical students is encouraging, the vaccination rate itself remains insufficient. Previous studies investigating influenza vaccination coverage among medical students worldwide reported vaccination rates varying from 4.7% in Iran to 86.3% in Canada [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Some studies found that clinical medical students were more likely to be vaccinated than those still in pre-clinical education [ 17 , 19 ], but this was not confirmed by subsequent investigations [ 13 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this apparent increase in the vaccination rate among medical students is encouraging, the vaccination rate itself remains insufficient. Previous studies investigating influenza vaccination coverage among medical students worldwide reported vaccination rates varying from 4.7% in Iran to 86.3% in Canada [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Some studies found that clinical medical students were more likely to be vaccinated than those still in pre-clinical education [ 17 , 19 ], but this was not confirmed by subsequent investigations [ 13 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…If people are motivated to receive vaccinations as students, they are likely to continue being vaccinated as HCWs in the future [ 11 ]. Studies show that vaccination coverage among medical students ranges from 4.7% in Iran to 86.3% in Canada (in various seasons) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Influenza vaccines are well-known, safe, and recommended by medical authorities, yet only a fraction of Polish medical students decide to be vaccinated.…”
Section: Introductionmentioning
confidence: 99%
“…5 However the study was consistent with the one by Martinez, which showed that the majority of the participants did not receive influenza vaccine annually, and also with a study conducted by Kawahara and Nishiura to explore influenza vaccine uptake and its determinants among Japanese university and college students, which stated that students belonging to medicine and healthcare related faculties were vaccinated three times more frequently than other students. 15 , 16 The marked difference might be attributed to the difference in the field of the study as the studies from health sciences field showed more vaccination percentage than studies form other fields.…”
Section: Discussionmentioning
confidence: 99%
“…Among students in all grades of medical education including freshmen and students training in medical and healthcare-related faculties were reported to have higher vaccination coverage than the others. 13 However, a comparison was not performed between the students with respect to their academic years in this study. Influenza vaccination rates are known to be quite low among Turkish HCWs.…”
Section: Influenza Vaccinementioning
confidence: 98%